Psychometric properties of the SRQ-Reading Motivation in primary students from Lima - Dammert, Martin (2024)
This study explored the psychometric properties of the Spanish version of the Self-Regulation Questionnaire Reading Motivation (SRQ-Reading Motivation) in the context of academic reading, specifically, in the school library. Participants were 235 students enrolled in fourth or fifth grade at a private school in Lima. This study analyzed the internal structure of the scale by means of confirmatory factor analysis. Results yielded a two-factor model indicating autonomous and controlled reading motivation. Findings obtained from convergent and discriminant validity were consistent with those expected. The reliability of the scores obtained in the scales was also adequate. Results and implications are discussed grounded in Self-Determination Theory’s bright and dark side of motivation.